Cecidomyiinae (Diptera, Cecidomyiidae) das restingas da Barra de Maricá, Itaipuaçu e Carapebus (Rio de Janeiro, Brasil): descrições e dados biológicos - Maia, Valéria Cid (1999)
At "restingas" of Barra de Maricá, Itaipuaçu and Carapebus, 108 species of Cecidomyiinae were found in association with 53 plant species distributed among 42 genera and 32 families. 93 Cecidomyiinae species were cecidogenous, 4 predators, 5 inquilines of galls and 6 had free living larvae . Gall maker species were associated with 47 plant species (36 genera and 28 families). The majority of the galls were leaf ones (63); 13 developed from bud; 9 occurred in inflorescence, closed flower or flower peduncle; 3 in fruits and 1 in clasper. The Myrtaceae were the first plant family in richness of galls followed by Burseraceae, Nyctaginaceae, Sapotaceae, Erythroxylaceae, Malpighiaceae and Solanaceae. 11 new genera and 14 new species of Cecidomyiinae were described (larva, pupa, male, female and gall), larva of 3 species and pupae of 2 others were described, 2 new combinations were proposed and new records of host plants and Iocalities registered. 79 Cecidomyiinae species were found at "restinga" of Barra de Maricá, 64 at Carapebus e 41 at Itaipuaçu. Sorensen index revealed that the "restingas" of Barra de Maricá and ltaipuçu are more similar in Cecidomyidae fauna, confirming a positive relation between geographical proximity and fauna similarity.